Effective strategies to recruit young adults into an online wellbeing intervention - Gaston Antezana (Frontiers Media S.A., 2015)
Background Implementing online interventions may be an effective way to support young people to improve their wellbeing. There is a need to identify effective and cost efficient strategies to successfully recruit young adults into such interventions. Objectives This paper will describe the outcomes of different methods for recruiting young adults (16-25) to the 'Online Wellbeing Centre', an online resource to assess wellbeing and access apps for mental health and general wellbeing. Methods Online and community strategies, which were of paid and unpaid nature, were utilised for recruiting participants aged between 16-25. Online paid strategies included 9 Facebook ads, 2 Twitter ads, 2 Google ads, and 1 YouTube ad. Online unpaid channels included Facebook and Twitter posts on the official pages of selected partner organisations, links on the websites of selected partner organisations, tailored messages and link via a University student learning portal, and bulk emails to various networks of young people. Unpaid community based recruitment strategies included a bulk email to various community contacts, and face-to-face contact via meetings and presentations in schools and mental health services. The one paid community based strategy was the use of a recruitment agency. All ads and posts were designed with final user input following principles of participatory methodology. All recruited participants were asked to complete a self-assessment of mood, energy levels, and sleep quality presented via visual analog scales, and also the Mental Health Continuum-Short Form assessment survey. Recruitment success via each of the strategies was descriptively analysed. Univariate analysis of variance was conducted to explore if self reported measures varied between paid and unpaid channels of recruitment. Results A total of 378 participants were recruited over a timeframe of 10 months. 26.7% of recruited participants were from paid channels with the recruitment agency and Facebook ads accounting for 15.6% and 8.5% respectively. Least effective paid strategies included Google ads and YouTube ads, each accounting for only 0.5% of participants. The average cost per participant recruited through paid channels was 85 AUD. Amongst unpaid channels Facebook posts were found to be the most effective recruitment avenues, accounting for 17.5% of all participant sign up. Advertising targeted to particular user groups was also effective: help seeking/health oriented young adults approached via partner's websites (Reachout.com, Young and Well CRC) accounted for 14.3%; University students were recruited using the Flinders University student learning portal accounted for 12.2%. Face to face community recruitment accounted for 6.6% of participants and community based targeted emails accounted for 6.9%. Participants recruited through paid channels scored lower on the Mental Health Continuum-Short Form assessment (p = 0.05), mood rating (p = 0.03) and sleep quality (p = 0.03), and were also found to be slightly younger (p = 0.06). Conclusions Several paid and unpaid channels to recruit young adults were explored in this study. There was a notable difference in success rate as well as demographics and clinical characteristics between unpaid and paid recruitment channels.